The influence of sports on the psychological state of employees from the perspective of the corporate culture - Yi Xuan Shang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
This research is conducted to determine, from the perspective of corporate culture, the effect of sports on the psychological state of employees. This study examined the employees of a business unit company, including frontline production personnel, office technicians, and company management personnel, to determine their health status and physical activity participation. The questionnaire was used to capture data for this study, and Smart PLS 3 was used to analyze the results. From the corporate culture perspective, the empirical findings supported sports' influence on employees' psychological state. This study presented novel conclusions regarding the impact of athletics on the psychological health of students. The research has contributed to expanding the corpus of knowledge with significant theoretical implications. The practical implications of this study are beneficial for enhancing the psychological well-being of employees within the corporate culture through athletics. Future studies are required to resolve the limitations of the current investigation.